Hubungan Antara Pola Pembinaan Dengan Kemampuan Interaksi Sosial Anak Di Panti Asuhan Al-Kautsar Muhammadiyah Kabupaten Padang Pariaman - Natsir , MHD.; Ediarma, Nur Salshabila (Universitas Negeri Padang, 2024)
This research is motivated by the lack of children's abilities in social interaction, and the lack of children in collaborating with other children or their peers, because many children are more concerned with themselves than collaborating to train social feelings. The aim of the research activity is to determine the description of: coaching patterns, children's social interaction abilities, and the relationship between coaching patterns and children's social interaction skills at the panti asuhan Al-Kautsar Muhammadiyah Pakandangan, Padang Pariaman Regency. The research was carried out using a quantitative approach with a correlational type. The research population is children who live at the Al-Kautsar Pakandangan Orphanage. Meanwhile, the research sample was taken using census techniques. The research instrument for collecting data uses a questionnaire. Data analysis techniques use percentage and rank order formulas. The research results show that: (1) The coaching pattern is categorized as poor; (2) Children's social interaction abilities are categorized as poor, and (3) There is a significant relationship between coaching patterns and children's social interaction abilities at the panti asuhan Al-Kautsar Muhammadiyah Pakandangan, Padang Pariaman Regency.